Pengembangan Lembar Kerja Siswa Berbasis Think-Talk-Write pada Mata Pelajaran Matematika - safriadi safriadi; Sitti Mania; Fitriani Nur; Andi Dian Angriani; M. Yusuf Tahir (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2022)
This study aims to produce mathematics worksheets for high school students that are in accordance with the characteristics of students and meet valid and practical criteria. This worksheet is expected to be used as one of the learning media for students to develop their special abilities in mathematics. This research is a research and development using the Instructional Development Model (MPI). The product developed in this study is a Think Talk Write (TTW)-based math worksheet. The data collection instrument used is a questionnaire. The data analysis technique used is the data analyzed using data analysis techniques of validity and practicality. The results showed that the TTW-based math worksheets that met the criteria were valid and practical. So it is recommended for further research in order to continue by reviewing its effectiveness in improving students' mathematical problem solving abilities.